PENGARUH ROTASI KERJA DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK SYARIAH NASIONAL KANTOR CABANG SURABAYA - Dwiyani Wahyuningtias; Ony Kurniawati; Titok Waskito Adi; Dedy Kunhadi (STIE Mahardhika, 2026)
This study aims to: (1) Analyze how job rotation affects employee performance at PT. Bank Syariah Nasional, Surabaya Branch Office; (2) Analyze the effect of job training on improving employee performance; and (3) Analyze the simultaneous effect of job rotation and job training on employee performance within the company. This study involved 75 respondents, all employees of PT. Bank Syariah Nasional, Surabaya Branch Office. Data were obtained by distributing questionnaires to the respondents. The collected data were then analyzed using multiple linear regression using SPSS software to obtain an overview of the relationships between the variables studied. The data processing results revealed several important findings. First, job rotation was shown to have a partial effect on employee performance. Second, job training also demonstrated a positive individual contribution to improving employee performance. Third, when these two variables were analyzed together, job rotation and job training were shown to have a significant effect on employee performance within the organization. These findings indicate that the appropriate implementation of job rotation and ongoing training programs play a crucial role in supporting the improvement of employee performance at PT. Bank Syariah Nasional, Surabaya Branch Office. The results of this study are expected to serve as a reference for management in evaluating and improving the effectiveness of human resource management. Furthermore, employee performance demonstrating optimal performance can serve as a basis for companies to provide awards or incentives as a form of appreciation and to maintain consistent work motivation.